s-cis and s-trans Conformers of Formic, Thioformic and - Fausto, R. (1989)
Ab initio SCF-MO calculations have been carried out for formic, thioformic and dithioformic acids using the 6-31G* basis set. Fully optimized geometries, atomic charges, relative stabilities and harmonic force fields for s-cis and s-trans conformers of these molecules have been determined and the effects of oxygen-by-sulphur substitution analysed. A realistic description of the molecular charge distribution can be reached by introducing a quantum-mechanical correction to the Mulliken atomic charges, derived from the 'charge'-'charge flux'-'overlap' (CCFO) model. Unlike reported theoretical results, the present ab initio calculations yield relative stabilities of the thioformic acid conformers in agreement with experiment [s-cis (thiol) > s-trans(thio1) > s-cis(thione) > s-trans(thione)]. The success of these ab initio calculations should be partially ascribed to the inclusion of polarization functions on all non-hydrogen atoms.